Entrepreneurial universities in the region: the force awakens?. Issue 1 (7th March 2016) - Culkin, Nigel
Abstract : Purpose: – The growth in popularity of the regional innovation system approach has, in part, been driven by the need for economies to respond to the after shocks of the global financial crisis. At the same time, the author sees the term anchor institutions are used increasingly to describe organisations that have an important presence in the local community and make some strategic contribution to the local economy. The purpose of this paper is to consider the needs of the micro and small business (MSB) ecosystem through the lens of the entrepreneurial university as a regional anchor institution. Design/methodology/approach: – Asheim et al . (2011) refers to regional innovation systems as, an emphasis on economic and social interaction between agents, spanning the public and private sectors to engender and diffuse innovation within regions embedded in wider national and global systems. According to Doloreux and Parto (2005) three dimensions underpin the use of the regional innovation systems concept, namely: the interactions between different actors in the innovation process, the role of institutions and the use of regional systems analysis to inform policy decisions. The author has drawn on contemporary literature on the entrepreneurial university, regional systems of innovation and institutions to explore some key qualities and problems around anchor Institutions, networks and national and local policy. Findings: – Following the Chancellor's Comprehensive Spending Review in November 2015 and post the changes in the Department of Business Innovation and Skills remit the author wants to highlight the way universities can take a lead role as an anchor institution within their region. The author argues that this role should include providing a wider range of formal and informal support, knowledge and resource for MSBs, alongside the usual SME suspects (Hart and Anyadike-Danes, 2014; Witty, 2013; Wilson, 2012). Based on my analysis and involvement in the the work of the eight Entrepreneurial Universities of the Year Award winners – during the author's time as President of ISBE – He suggested four different ways in which collaboration might be enhanced to ensure MSBs make maximum use of the advice and support on offer from universities playing this anchor role. Originality/value: – The results emerging from this work suggest a need for regional policy makers to embrace a innovation-supportive culture, which actually enables firms and systems to evolve over time would be far more effective than those proposed in the latest Comprehensive Spending Review. The outcomes of which will see some of the most robustly evaluated programmes, designed to support small firm growth, closed down and replaced by a commitment (by government) to secure a strong, growing economy, cutting of more red tape and extending small business rate relief for an extra year (Mole, 2015).